The Abundance and Spatial Distribution of Soft Sediment Communities in Tanjung Bungah, Malaysia: A Preliminary Study - Nur Aqilah Muhamad Darif,; Nur Shakila Abdul Samad,; Sazlina Salleh,; Mahadi Mohammad,; Noor Alia Ahmad Nordin,; Aysha Mariam Mohamed Javeed,; Michelle Glory G Jonik,; Muhamad Hilal Mohd Zainudin, (Tropical Life Sciences Research, 2016)
Benthic faunal communities are important components in the intertidal zones. The diversity and abundance of the benthic communities are subjected to different natural and anthropogenic disturbances. The study was conducted as one off sampling on 6th November 2013 (1) to investigate the abundance and distribution of soft sediment communities in relation to environmental variables and (2) investigate the changes of population structure and diversity using spatial scales of 1 m, 10 m, and 100 m. Results indicated a total of 110 individuals of macrobenthos consisting of 7 different groups (Annelida, Bivalvia, Crustacea, Gastropoda, Nematoda, Nemertea, Polychaeta) and 4 different groups of meiobenthos (Copepoda, Nematoda, Ostracoda, Polychaeta) consisting 920 individuals were recorded. Dissolved oxygen played the most significant role in affecting the distribution of soft sediment communities while ammonia concentrations only affected marcobenthic organisms. However, sediment grain size did not show significant correlation (p>0.05) on soft sediment communities. Hence, understanding how different properties of benthos respond to changes in environmental variables is crucial in determining how the impacts on the sediment are tolerated by the benthic organisms.